An annotated catalog of the Iranian Miridae (Hemiptera: Heteroptera: Cimicomorpha) - Ghahari, Hassan; Chérot, Frédéric (Zootaxa, 2014)
An updated list of Iranian Miridae Hahn, 1833 is provided and discussed. Seven subfamilies (Bryocorinae, Cylapinae, Deraeocorinae, Isometopinae, Mirinae, Orthotylinae, and Phylinae), 140 genera, and 498 species are confirmed from Iran. Phytocoris (Stictophytocoris) meridionalis (Herrich-Schaeffer, 1835), is newly recorded from Iran. The possible presence in the country of 28 additional species is briefly analyzed.